Future trends in digital narratives of consumer behavior for Takaful through Islamic marketing - Iqbal, Muhammad Nawaz; Jan, Muhammad Tahir (IGI Global, 2025)
The focus of this chapter is on the future direction of the digital narratives that are key to consumer management for Takaful under Islamic marketing. All these while, the Takaful industry, which is based on Islamic principles, is subjected to new challenges and opportunities in order to transform the marketing message towards the introduction of digital transformation into the appropriate ethical and cultural values, interpreted by consumers. It highlights how digital storytelling is critical to develop consumer trust and engagement to help Takaful consumer and sustain engagement, continue to advance consumer demand for transparency, values based communications and Islamic precepts significantly impact the decision to select financial services. The chapter provides a further discussion on how technological opportunities, including the artificial intelligence, big data, and social media, can be utilized in the construction of culturally appropriate stories.